Analisis Prediksi Financial Distress pada PT Indofarma Tbk (Persero) - Pennynauli, Kescya Ananopan (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to analyze financial distress prediction in PT Indofarma Tbk (Persero) using the Grover, Taffler, and Springate models. The study employs a quantitative descriptive approach using secondary data obtained from the financial statements of PT Indofarma Tbk (Persero) during the 2014–2023 period. The sample was selected using purposive sampling, and the data were analyzed using Microsoft Excel. The results show that the Grover model classifies eight years of observation as healthy and two years, namely 2022 and 2023, as financial distress. The Taffler model classifies seven years of observation as healthy, one year, namely 2017, as a gray area, and two years, namely 2022 and 2023, as financial distress. Meanwhile, the Springate model classifies all ten years of observation as financial distress. These findings indicate that the Springate model is the most sensitive model in detecting financial distress in PT Indofarma Tbk (Persero), while the Grover and Taffler models identify severe financial distress mainly in the last two years of observation.